Design and development of an interlligengt paper, plastic and bottle segregation (prototype) system - Maheswaran, Degarajan
The project is intended to reduce a major portion of unrecyclable materials especially paper and plastics are left uncollected from domestic wastes due to lack of efficient and economical waste sorting mechanism.